WISATAWAN MILENIAL: PANGSA PASAR POTENSIAL UNTUK PENGEMBANGAN PARIWISATA DI KABUPATEN BULELENG - Rai Suastini; I Wayan Sudiarta (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2022)
This research was conducted to provide an alternative for local governments to choose millennial tourists as a market share. Factors such as image, characteristics and motivation in traveling also support the development of this tourism. A suitable marketing strategy for millennial tourists is to use the services of influencers. This research is a qualitative descriptive study. The primary data in this study were sourced from observations, interviews and literature studies, while the secondary data were from scientific journals and books that assisted in this research. The approach used in this research is the sociology of tourism approach. The data collected is then reduced, selected data that can support it, followed by carrying out the analysis and the last step is drawing conclusions.Keywords: Tourists, Millennials, Potential, Tourism